THE FORMATION OF INVESTMENT POLICY: A TOOL OF SUCCESSFUL ECONOMIC DEVELOPMENT THE NORTH CAUCASIAN FEDERAL DISTRICT - Vitaly Zhuravel; Vladimir Grechko (Вестник Северо-Кавказского федерального университета)
In the article the analysis of the gross regional product (GRP) in the North Caucasus Federal district, i nvestigated the investment potential and the current state of investment activity in the North Caucasus Federal district, the assessment of investments in fixed capital, as well as the proposed principles for the formation of successful investment policy in the North Caucasus Federal district.